Preliminary investigation into tree dryness in Hevea brasiliensis (Wild. Ex Adr. De Juss) Muell. Arg. by path analysis of tree dryness and latex parameters. - Omokhafe K O (Tropicultura, 2001)
The correlation between tree dryness and four latex parameters was studied in eleven clones of Hevea brasiliensis at Etche, Rivers State, Nigeria. The latex parameters used for evaluation were initial volume, initial flow rate, final volume and plugging index, with tree dryness as the dependent factor. Estimates of direct and indirect effects of each of the latex parameters on tree dryness were calculated through linear correlation and path analyses. The correlation coefficient between initial volume and initial flow rate was 1.00, and both characters had the same correlation coefficients with other latex parameters and tree dryness. This implies that initial volume and initial flow rate are alternatives for evaluation of correlation between latex parameters and tree dryness. There was significant correlation between initial volume, initial flow rate and tree dryness at = -0.52, and high indirect effect of initial volume and initial flow rate through final volume. In addition, despite the low correlation coefficient of = -0.20 between final volume and tree dryness, the direct effect of final volume on tree dryness was high at 0.812. Final volume is, therefore, an important factor in the incidence of tree dryness.
Source Year: 2002
Keywords: Hevea brasiliensis; Latex parameters; Tree dryness